Naturale, artificiale e virtuale: il fenomeno complesso della vita (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The complexity of the phenomenon of life emerges in its definition: the term “life” is ambiguous in its meaning and for its value. At present, converging technologies and forms of life’s hybridization seem to reflect the tendency of letting converge increasingly natural, artificial and virtual life. Philosophical reflection can allow an epistemological, anthropological and ethical analysis of some main issues related to the recent evolution and application of neuroscience and neurotechnologies.
Keywords: Biological and artificial life; converging technologies; artificial neurons; enhancement; neuroethics